1897
DOI: 10.1002/cber.18970300389
|View full text |Cite
|
Sign up to set email alerts
|

Ueber ein Spaltungs‐product des Arginins

Abstract: Der Korper erwies sich durch Zusammensetzung und Eigenschaften ebenfalls als identisch mit dern kiirzlich aus Oxanilid und Essigsaureanhydrid dargestellten V i n y l i d e n o x a n i l i d I). A 1 k o h o l i s c h es Ka li spaltet in O x a l s a u r e und A e t h e n y l d i p b e n y l a m i d i n , das aua Ligroi'n in verfilzten Nadeln vom Schmp. 13 1 krystallisirt. Analyse: Ber. fiir C I~H I~N~. Procente: C SO.O, H 6.7, N 13.3. Gef. ')) 80.3, SO.l, x 7.0, G.7,)) 13.6. Mo1.-Gew. : Ber. 210. Gef. 200, 200, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1898
1898
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…2 Data are from Beaumier [53] for healthy infants. 3 Data are from Castillo et al [54]. 4 Data on plasma concentrations of citrulline and arginine are from Flynn and Wu [61].…”
Section: Arginine Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…2 Data are from Beaumier [53] for healthy infants. 3 Data are from Castillo et al [54]. 4 Data on plasma concentrations of citrulline and arginine are from Flynn and Wu [61].…”
Section: Arginine Synthesismentioning
confidence: 99%
“…This interesting amino acid was first isolated from lupin seedlings in 1886 [1], and soon afterwards (1895) was identified as a component of animal proteins [2]. The structure of arginine was established by alkaline hydrolysis to yield ornithine and urea in 1897 [3] and by synthesis from benzoylornithine in 1910 [4]. Subsequently, arginine was found in 1924 to be a major amino acid in the basic proteins of fish sperm [5], and its synthesis by mammals was deduced in the classic nutrition studies of W. C. Rose and his colleagues in 1930 [6].…”
Section: Introductionmentioning
confidence: 99%
“…Kossel demonstrated (240) that it was unusually plentiful in the basic protein-like substances he had prepared from fish sperm. In 1897 Schulze and Winterstein (246,247) found that arginine, when heated with alkalies, yielded ornithine in addition to urea. This was isolated as its dibenzoyl compound, the ornithuric acid (6pvi6os, bird; urina, urine) of Jaffé (239).…”
Section: Schulze Andmentioning
confidence: 99%
“…This substance was identified in a later paper(246) as ornithine by means of its dibenzoyl compound, ornithuric acid, discovered many years before by Jaffé(239).…”
mentioning
confidence: 94%
“…L-arginin (α-amino-δ-guanidine valeric acid) was isolated in 1866 by Schultz and Steiger from white (etiolated) sprouts of lupin (Lupinus) [33]. Arginine structure was established through its hydrolysis in alkali environment (resulting from which ornithine and urea were received) [34], as well as from benzoyl ornithine through its synthesis [35]. During acidic hydrolysis of proteins arginine may disintegrate up to ornithine; arginine transformation into citrulline during hydrolysis in alkali medium is reported from literature as well [36].…”
Section: Introductionmentioning
confidence: 99%